DETERMINAN FREKUENSI KONSUMSI MINUMAN BERPEMANIS DALAM KEMASAN DI SMAIT MAHAD RAHMANIYAH AL ISLAMY - musniati, nia; Zahrani, Aisyah (Jurnal Kesehatan Madani Medika, 2025)
Consumption of sugar-sweetened beverages (SSBs) among adolescents has shown an increasing trend. Excessive intake of SSBs can increase the risk of non-communicable diseases (NCDs). This study aimed to analyze the factors associated with the frequency of SSB consumption among students at SMAIT Mahad Rahmaniyah Al Islamy, Bogor Regency, West Java, in 2025. A cross-sectional study design was employed using primary data collected through questionnaires distributed to students. The sampling technique applied was total sampling, involving 115 respondents. Data were collected using a validated and reliable questionnaire. Data analysis consisted of univariate analysis, bivariate analysis using the Chi-square test, and multivariate analysis using multiple logistic regression. The results showed that taste preference, pocket money, accessibility, peer influence, and parental control were significantly associated with the frequency of SSB consumption (p < 0.05). The factor most strongly associated with consumption frequency was pocket money. In conclusion, the determinants of SSB consumption frequency among adolescents include taste preference, pocket money, accessibility, peer influence, and parental control. Interventions are needed to promote healthy beverage preferences and enhance social control over SSB consumption among adolescents.